1991
DOI: 10.2105/ajph.81.5.623
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 prevalence in selected Tijuana sub-populations.

Abstract: To assess the prevalence of HIV-1 (human immunodeficiency virus) infection among high-risk populations in Tijuana, Mexico, HIV-1 antibody status was determined and information on risk behavior was obtained from 1,069 individuals in three high-risk groups. The prevalence of HIV-1 among 415 prostitutes was 0.5 percent; 410 prisoners, 1.2 percent; 233 homosexual/bisexual men, 11.6 percent; and 106 intravenous drug abusers, 1.9 percent. The potential for spread of HIV-1 exists in Tijuana despite the current relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 7 publications
2
14
1
1
Order By: Relevance
“…HIV-1 seroprevalence in IDUs in Tijuana recruited through RDS was similar to that found in IDUs studied by Güereña-Burgueño et al41 in the early 1990s and in a study by Magis-Rodriguez et al42 in 2003 that used time-location sampling methods, although the absolute number of HIV-positive cases was too low to perform reliable RDS corrections. In contrast to HIV, syphilis prevalence was extremely high, especially in women and in Tijuana.…”
Section: Discussionsupporting
confidence: 83%
“…HIV-1 seroprevalence in IDUs in Tijuana recruited through RDS was similar to that found in IDUs studied by Güereña-Burgueño et al41 in the early 1990s and in a study by Magis-Rodriguez et al42 in 2003 that used time-location sampling methods, although the absolute number of HIV-positive cases was too low to perform reliable RDS corrections. In contrast to HIV, syphilis prevalence was extremely high, especially in women and in Tijuana.…”
Section: Discussionsupporting
confidence: 83%
“…In other homosexual populations similar prevalence rates have been found (Morales et al 1994) and even higher rates were found in North Carolina (Schoenbach et al 1993), a state wthin the United States with low overall STD incidence. Our prevalence was higher than those found in San Francisco, within the United States (Lemp et al 1994), Amsterdam in The Netherlands (Keet et al 1993) and Tijuana, Mexico (Güerenã-Burgueño et al 1991) where the rates, in similar populations, were 9, 5 and 12%, respectively.…”
Section: Resultscontrasting
confidence: 59%
“…High and low estimates of HIV-infected MSM were obtained from published local survey results. 16,22,23 Cross-sectional serosurveys conducted by CENSIDA in 2003 20 and by our group in 2005 24 were used to estimate the HIV prevalence range among IDUs. 20 Recent data from an ongoing study of FSWs provided the likely range of HIV prevalence in female sex workers.…”
Section: Resultsmentioning
confidence: 99%